If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13.7b + -3 = 3 + -43b Reorder the terms: -3 + 13.7b = 3 + -43b Solving -3 + 13.7b = 3 + -43b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '43b' to each side of the equation. -3 + 13.7b + 43b = 3 + -43b + 43b Combine like terms: 13.7b + 43b = 56.7b -3 + 56.7b = 3 + -43b + 43b Combine like terms: -43b + 43b = 0 -3 + 56.7b = 3 + 0 -3 + 56.7b = 3 Add '3' to each side of the equation. -3 + 3 + 56.7b = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 56.7b = 3 + 3 56.7b = 3 + 3 Combine like terms: 3 + 3 = 6 56.7b = 6 Divide each side by '56.7'. b = 0.1058201058 Simplifying b = 0.1058201058
| 48=12xn | | 19=5a-6 | | -189=-2x-3(7x+17) | | 81-x=94-2x | | 99.60=9.1a+72.3 | | 36=9(r-2) | | 70-3x=130-43x | | 35+42=12+x | | 9x+9=8x+4 | | 5x+7(7+3x)=4(9-8)+7 | | X+19=7+20 | | 99=98s+1 | | 8a^2+10ab^2+4ab+5b^3=0 | | 81-2x=92-3x | | 28=2w+24 | | f(0)=2x^3-5 | | 1.5sin(x)=sin(3x) | | 5x-17=12x-4 | | 2y^2+8y+2=0 | | 2(x+7)-6=x+15 | | (2x^3y^2)= | | (1-4y)(5-y)= | | 14s-10s=12 | | 2x+x+15=4x+10 | | 2c-7-8c=17 | | 4x+5=-37-10x# | | Y=17x+22 | | 10x+10x=20 | | 2x+2(3x+4)=56 | | 24+2(5+5x)+15x-1=208 | | 24+3(5+5x)+15x-1=208 | | 124-37=x |